2021
DOI: 10.7554/elife.72943
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets and ferritin heavy chain: a devilish liaison in human cancer cell radioresistance

Abstract: Although much progress has been made in cancer treatment, the molecular mechanisms underlying cancer radioresistance (RR) as well as the biological signatures of radioresistant cancer cells still need to be clarified. In this regard, we discovered that breast, bladder, lung, neuroglioma and prostate 6 Gy X-ray resistant cancer cells were characterized by an increase of Lipid Droplet (LD) number and that the cells containing highest LDs showed the highest clonogenic potential after irradiation. Moreover, we obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…It has been shown that RR cancer cells can activate several antioxidant pathways in order to reduce ROS generated by radiation therapy. In this context, LDs can play a crucial role to avoid lipotoxicity and retain the cell homeostasis, favoring DNA repair and promoting cell survival [39,[42][43][44]. In our conditions, while MCF7 cells were presumably able to deal with the oxidative stress induced shortly after ionizing radiation, they showed increased ROS levels after 72 h of PF-06424439 which resulted further increased 72 h after IR both in cells only pretreated with PF-06424439 and in cells subjected to combined treatments.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It has been shown that RR cancer cells can activate several antioxidant pathways in order to reduce ROS generated by radiation therapy. In this context, LDs can play a crucial role to avoid lipotoxicity and retain the cell homeostasis, favoring DNA repair and promoting cell survival [39,[42][43][44]. In our conditions, while MCF7 cells were presumably able to deal with the oxidative stress induced shortly after ionizing radiation, they showed increased ROS levels after 72 h of PF-06424439 which resulted further increased 72 h after IR both in cells only pretreated with PF-06424439 and in cells subjected to combined treatments.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, some evidences demonstrated that the LD amount is proportional to the degree of tumorigenicity in breast cancer cell lines [21], sustaining that the aberrant accumulation of these organelles represents one of the main features of BCSCs [24]. Additionally, we have recently shown that in different cancer tissues, including breast, the most radioresistant cancer cells were characterized by a higher LD expression, and that the LD content was tightly regulated by the ferritin heavy chain 1 (FTH1) [39].…”
Section: Discussionmentioning
confidence: 93%
“…LDs have now been suggested to be involved in all processes of cancer development, including initiation, promotion, and progression [ 111 ]. The hypotheses regarding LD function in cancer cells are numerous, i.e., promoting tumor proliferation [ 153 , 154 , 155 ], driving epithelial–mesenchymal transition (EMT) [ 115 , 156 , 157 ], mediating radio-resistance [ 158 , 159 ] and chemo-resistance [ 160 , 161 , 162 , 163 ], maintaining cancer cell stemness [ 164 , 165 , 166 ], and avoiding immune destruction [ 167 , 168 , 169 ]. Nevertheless, these hypotheses need to be experimentally validated.…”
Section: Inhibiting Ld Formation For Gbm Therapymentioning
confidence: 99%
“…Mechanistically, acetyl-CoA, which is one of the main metabolites of FAO, upregulates the expression of CD47 by acetylating RelA K310 [ 47 ]. It is also notable that the crosstalk between lipid droplets and iron metabolism makes cancer cells more radioresistant [ 50 ]. In hepatocellular carcinoma (HCC) cells, the integration of glucose and cardiolipin anabolism, which is regulated by the mTORC1/HIF-1α/SREBP1 axis, promotes resistance to radiation by repressing cytochrome c extrusion [ 51 ].…”
Section: Molecular Mechanisms Of Radioresistance In Tumor Cellsmentioning
confidence: 99%